Cenni sulla centralità del pulchrum nell’intreccio dei trascendentali in Gadamer - Ascencio, L.C., Juan Gabriel (Alpha Omega, 2017)
Summary: This reflection takes its point of departure from the final part of Truth and Method, where Gadamer associates the transcendental notion of beauty, as it had been elaborated by Plato, with his universal hermeneutic. Beauty and goodness are shown to be united in Gadamer’s reflection on Philebo, thereby demonstrating, according to Gadamer, the ontological function of beauty as mediation between idea and phenomenon. In the end, this mediation makes it possible to establish an analogy between beauty and language in terms of their capacity for mediation: beauty is the mediation of the good, which in itself is inaccessible, in the same way that linguistic understanding is the mediation of the truth, which in itself is inaccessible. Consequently, Gadamer’s reflection on beauty appears to be united to that on the good and on truth. Key words: Gadamer, beauty, good, truth, language, Philebus, language, mediation. Parole chiave: Gadamer, bello, bene, verità, linguaggio, Filebo, linguaggio, mediazione.